Research on Stability Evaluation of Landslide Sourcein Bayi Gully Basin in Wenchuan Earthquake Area - WANG Xiaodi (Renmin Zhujiang)
After the Wenchuan earthquake, a large number of loose materials produced by co-seismiclandslide deposited on the slope, which serve as rich material source for the secondary geo-hazards, such as landslide and debris flow, therefore, the stability evaluation of the landslidesource in the debris flow basin is of great significance for the prevention and warning of debrisflow activities. Taking Bayi Gully after the earthquake as the research object, this paperevaluates the stability of landslide source based on OpenLISEM model. The results show that theinstability of landslide source accounted for 6.28% and the under-stability of landslide sourceaccounted for 55.28%, it indicated that the stability of landslide source in Bayi Gully after theearthquake was poor, the landslide source was easy to slide under rainfall, and the frequency oflandslide and debris flow activities was high. At the same time, this paper discusses the spatialdistribution characteristics of landslide source with different stability levels on differenttopographic factors based on GIS. The results indicate that the distributed dominant elevation,slope, slope direction and distance from the gully of the landslide source in the unstable statewere 1 500~2 100 m, 45~60°, slightly southward, 50~100 m. The research model has certainapplicability and reference in the risk assessment of landslide and debris flow in debris flowbasin after the earthquake.